The role of meteorology on different sized aerosol fractions (PM 10, PM 2.5, PM 2.5-10) - Pateraki, S.a b; Asimakopoulos, D.N.b; Flocas, H.A.b; Maggos, T.a; Vasilakos, C.a (Science of the Total Environment, 2012)
The scope of the present study is to assess the influence of meteorology on different diameter particles (PM 10, PM 2.5, PM 2.5-10) during a 53months long experimental campaign at an urban Mediterranean area. Except for the investigation of the wind, temperature and relative humidity role, day by day synoptic conditions were classified over the Attica peninsula in order to explore as well, the role of the synoptic scale atmospheric circulation. The strong dependence of the aerosols character on their various sources, not only explain the different diameter particles behavior and their differentiation with the inorganic pollutants but also highlights the need for an effective emission policy. High PM 10 and PM 2.5-10 concentrations found to be closely related to the southwesterly regime, suggesting long range transport from the ’polluted’ south sector while the general prevalence of the secondary particles generation revealed the health hazard. PM 2.5 showed a weaker correlation than the bigger particles with both the circulation patterns and the parameters’ fluctuations. Temporal pollutants variations were clearly governed by the emissions patterns while the low wind speed was not necessarily a good indicator of high concentration levels. Finally it was found that only during the open/close anticyclonic days and the southwesterly wind regime the morning levels were continuously higher than those of the night. © 2012 Elsevier B.V.
Keywords: aerosol; Aerosols; Air Pollutants; Air pollution; air pollution control; ambient air; article; Atmospheric aerosols; atmospheric circulation; Atmospherics; Circulation patterns; Cities; Climatology; concentration (parameters); controlled study; correlation; Environmental Monitoring; Experimental campaign; Greece; health hazard; Health hazards; High concentration; humidity; inorganic compound; Inorganic pollutants; long range transport; Low wind speed; Mediterranean areas; Mediterranean Region; Meteorological parameters; Meteorology; particle size; Particulate matter; pollutant; Pollution; Prevalence; priority journal; Relative humidity; sea; Seasons; Secondary particles; South-westerly winds; Synoptic conditions; temperature; Temperature and relative humidity; temporal analysis; Weather; wind erosion; wind velocity